ROBOTIC-ASSISTED KIDNEY TRANSPLANTATION: A REVIEW - Prasetyo, Dimas Tri; Birowo, Ponco; Hamid, Agus Rizal Ardy Hariandy; Wahyudi, Irfan; Rodjani, Arry; Mochtar, Chaidir; Rasyid, Nur (Indonesian Urological Association, 2018)
Objective: To discuss about kidney transplantation (KT), primarily on robotic-assisted kidney transplantation (RAKT) and to present the current updates on RAKT techniques performed by different centres worldwide. Material & methods: We searched and compiled various literatures on RAKT, focussing on different techniques used to perform the procedure. All the references cited in this review are indexed in PubMed or Scopus. Results: Since the first successful kidney allograft transplantation in human was performed in 1954, KT has become the preferred treatment modality for patients with end-stage renal disease (ESRD) seeking a more definitive outcome and better quality of life. Over the years, newer techniques of KT have been introduced, including minimally-invasive laparoscopic KT. However, laparoscopic KT has its own limitations, which include loss of hand-eye coordination and poor ergonomics for the surgeon. RAKT offers the same benefits as laparoscopic KT without its limitations. There are several transplantation centres worldwide performing RAKT regularly. The differences in RAKT technique between these centres are regarding patient’s position during surgery, location of incision for graft placement, use of regional hypothermia, and techniques of graft placement and ureteric reimplantation. Conclusion: The invention of RAKT as a minimally-invasive KT technique has enabled surgeon to perform surgeries when the operative field is deep and narrow and when fine dissection and microsuturing are required.